Utilizing the Facebook Live Streaming Feature in Services of the Gmim Pniel Tuna Worship in Manado, Wonasa, Kombos Area - Rondonuwu, Sintje Aneke; Tatimu, Ventje; Kalesaran, Edmon Royan (Journal of Asian Multicultural Research for Social Sciences Study, 2023)
The development of information technology is currently so rapid, along with the presence of various kinds of communication technology, the internet and its applications. Access to information in the current digital era can be received from various kinds of gadgets, including smartphones and PC computers to laptops. The emergence of the corona virus or covid-19 greatly influenced various aspects of human life in this world, both economically, socially, health, and so on, various efforts were made by all countries in the world including Indonesia to overcome the covid-19 problem. The impact of the spread of Covid-19 has also affected the congregation's worship process, one way that can be done is to take advantage of the development of ICT (Information Communication Technology) through the zoom application, so that the congregation can worship from home. Utilizing the Facebook live streaming feature in online worship can reduce the spread of the corona virus because there are no crowds. However, other problems still arise, related to how to use zoom by the congregation at GMIM PNILE Tuna Manado, Wonasa, Kombos Regions. There are still many complaints from the public or congregation related to the use of zoom, starting from bad network, how to use zoom and up to data quota limitations, and many other things that become obstacles in using zoom in worship, and the impact is also totality in worship online is reduced.